Measurements of the 277 nm photon detection efficiency of the OnSemi MicroFJ-60035 silicon photomultiplier. (December 2020) - Bogdanov, A A; Tuboltsev, Yu V; Chichagov, Yu V; Losev, S N; Sokolovskii, G S; Krassilchtchikov, A M; Kholupenko, E E
Abstract: The article describes a method for absolute calibration of the photon detection efficiency of the OnSemi/SensL MicroFJ-60035 silicon photomultiplier by the Newport Power/Energy Meter 841-PE with the 883-UV photodiode sensor head, and the PicoQuant PLS-270 fast diode source of 277 nm ultraviolet emission. The dependences of the power of the detected emission and the number of ultraviolet photons on the distance to the source were obtained. The photon detection efficiency of the silicon photomultiplier was measured to be approximately 8% compared to the 9.6% level claimed by the manufacturer. It was also shown that, within the experimental setup, absorption of the 277 nm emission at paths in the air shorter than 1 m is not significant, and the angular distribution of the emission source is homogeneous. The obtained three-dimensional calibration surface of the dependence of the irradiance on the distance to the detector and the source intensity will be employed for development of a novel camera of the TAIGA-IACT telescope array.